Marketing Strategy of Sharia Bank Products Using a Value-Based Islamic Marketing Approach - Vindi Elliawati; Nabila Azura Qothrunnada (Jurnal Ekonomi islam and Manajemen, 2025)
The rise of ethical consumerism presents a compelling challenge for Sharia banks to move beyond conventional marketing approaches and embed Islamic values, specifically Akhlaq (moral character), into their core strategic frameworks. This study develops a Value-Based Islamic Marketing (VBIM) framework that integrates the objectives of Maqasid al-Sharia (Islamic legal goals) with contemporary marketing analytics to better align business practices with spiritual and ethical principles. Employing a mixed-methods approach, qualitative case studies of three leading Islamic banks provide in-depth insights into current organizational practices and challenges, while a quantitative survey involving 400 customers measures the impact of VBIM on customer-related outcomes. Empirical findings reveal that VBIM significantly enhances customer loyalty by 37% and brand trust by 52%, demonstrating the efficacy of value-driven marketing grounded in Islamic ethics. However, successful implementation demands organizational transformation through Tawhidic realignment—reorienting the institution’s mindset toward the oneness of God (Tawhid), which integrates spirituality with business objectives. The study proposes a dual-axis model balancing spiritual fulfillment and market competitiveness, illustrating that Islamic banks can achieve sustainable growth by harmonizing ethical commitments with performance metrics. This framework offers practical guidance for Islamic financial institutions seeking to differentiate themselves in increasingly value-conscious markets while strengthening their authenticity and stakeholder engagement. The research contributes to the evolving discourse on Islamic marketing by providing a novel, empirically supported model that bridges traditional Islamic jurisprudence and modern marketing science.